FORMULATION AND PHYSICOCHEMICAL EVALUATION OF NANOSTRUCTURED LIPID CARRIER FOR CODELIVERY OF CLOTRIMAZOLE AND CIPROFLOXACIN - Sharma, Arun; Sood, Anikate; Mehta, Vineet; Malairaman, Udayabanu (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The purpose of this research was to formulate nanostructured lipid carrier system (NLCs) in such a way that they can be applied for bacterial as well as fungal infectious diseases. Methods: To achieve the prime objective, varying concentrations of clotrimazole (CLZ) and ciprofloxacin (CIPRO) were selected for formulations. Stearic acid (solid lipid polymer), oleic acid (liquid lipid polymer), and polyvinyl alcohol (surfactant) were utilized for formulating NLCs through solvent diffusion technique. NLCs were characterized for their surface morphology, Fourier transform infrared spectroscopy (FTIR) drug-polymer interaction, particle size distribution, zeta potential, loading capacity, drug entrapment efficacy (EE), and in vitro drug release profile. Results: NLCs were fabricated with size range varying from 276 nm to 564 nm, possessing smooth spherical morphology. No drug-polymer interaction was observed through FTIR analysis. The highest drug EE for CLZ and CIPRO was found to be 78.6% and 65.8%, respectively. Formulated NLCs depict the biphasic release profile with initial burst release of 40% within 2 hrs followed by controlled release. Conclusion: Better homing of drug molecules and controlled drug release through formulated NLCs makes them suitable carrier system for various anti-microbial and anti-fungal applications. Keywords: Nanostructured lipid carries, Clotrimazole, Ciprofloxacin, Solvent diffusion method, In vitro release.